Evaluasi Penerapan Arsitektur Tropis pada Gedung- Gedung Kantor Pemerintahan di Banda Aceh - Muhammad Yanis; Riza Priandi; Laila Qadri (Universitas Syiah Kuala, 2023)
Global warming and limited energy sources are problems that have been faced for the last 20 years. Energy savings can be made by utilizing natural lighting through architectural elements in buildings such as facades (walls, windows and roofs) in order to save a building's energy. The orientation and width of the window greatly affect the amount of incoming light. Indonesia is an area that has a tropical climate so that the availability of light is abundant, as well as in the city of Banda Aceh. Office buildings in Banda Aceh City have different functions and activities so that the need for light used in buildings will also differ according to their activities. This research is motivated by the different formations of office facades in Banda Aceh City, and have their own characteristics in the appearance of the building. The attractive and unique appearance of the facade is taken into consideration as well as the reason why this topic was raised as a research topic. This study aims to analyze and find out the elements of tropical architecture on the facades of office buildings in Banda Aceh. Here, researchers take samples of facades from three buildings in Banda Aceh for analysis on whether their tropical application meets standards or is just an attractive design appearance. The research method used is descriptive qualitative method which in practice begins with field observations or observations and is supported by literature studies. The results of the study can be concluded that the facade appearance of buildings tends to use a minimalist facade without any variation except a little in adjustment to the minimalist facade concept in tropical climate areas.